Xenia Hausner : true lies - Lahner, Elsy; Schröder, Klaus Albrecht; Hausner, Xenia (Ausstellung der Albertina, 2020)
Xenia Hausner is one of the most important Austrian woman artists of our time. This decorative volume focuses on the aspect of stagecraft which characterises all her works. Starting from the early works from the 1990s to her most recent moving Exiles series, the publication lures us into the mysterious world of inter-personal relationships.0The artist, who previously worked as a set designer, constructs three-dimensional settings for her pictures in her studio beforehand. Fragments of cars or train compartments become backdrops, and mundane everyday objects become co-actors in her quirky comic strips. The artist confronts us through staged excerpts with the contradictions inherent within ourselves, with facets which we do not reveal to the outside world. The fiction is what permits her to search with a penetrating vision for the true heart of the matter and to reveal it in her pictures.00Exhibition: Albertina Museum, Vienna, Austria (06.05. - 06.09.2020).